Plastic cannulas mitigate arteriovenous fistula stenosis by suppressing the CFB-mediated inflammatory cascade - Zhang, Dongjuan; Kong, Deyang; Zhao, MingMing; Ou, Zhanci; Ma, Lu; Qi, Ka; Yang, Yang (Frontiers in Immunology, 2025)
BackgroundThe choice of an appropriate cannulation technique should be important to increase the possibility of better outcomes in terms of arteriovenous fistulas (AVF) survival and comfort of the patient undergoing hemodialysis.MethodsIt is a retrospective study and microarray analysis was conducted to identify differentially expressed genes (DEGs) between failing and control access samples. Sixty-four patients who underwent early cannulation (3–4 weeks after AVF creation) were enrolled and divided into two groups: a plastic cannula group (n = 33) and a metal needle group (n = 31). Comparisons were made between the groups regarding complement components, blood flow, access intimal hyperplasia, and inflammatory cell infiltration.Results(1) AVF failure occurred in 13 patients (20.3%) over a mean follow-up of 241 ± 105 days. (2) Complement B factor (CFB) levels showed significant changes within the first two weeks post-cannulation. (3) Fluctuations in CFB strongly correlated with changes in AVF blood flow during follow-up. (4) CFB variation independently predicted AVF failure, with a hazard ratio of 4.54 (95% CI, 1.21–16.99). (5) The plastic cannula group exhibited significantly lower CFB expression in both blood and outflow access, along with marked improvements in intimal hyperplasia and inflammatory cell infiltration. (6) Compared with the metal needle group, serum from the plastic cannula more significantly induced endothelial cell proliferation and nitric oxide production, with CFB playing a critical role.ConclusionsThe alternative complement pathway is significantly activated during initial AVF cannulation, with excessive CFB production contributing substantially to AVF failure. The use of plastic cannulas may improve long-term AVF patency by mitigating endothelial dysfunction and inhibiting inflammatory cell infiltration through suppression of CFB generation.